2018
DOI: 10.1002/humu.23652
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 and BRCA2 5′ noncoding region variants identified in breast cancer patients alter promoter activity and protein binding

Abstract: The widespread use of next generation sequencing for clinical testing is detecting an escalating number of variants in noncoding regions of the genome. The clinical significance of the majority of these variants is currently unknown, which presents a significant clinical challenge. We have screened over 6,000 early‐onset and/or familial breast cancer (BC) cases collected by the ENIGMA consortium for sequence variants in the 5′ noncoding regions of BC susceptibility genes BRCA1 and BRCA2, and identified 141 rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…We and others have screened BRCA1 and BRCA2 promoters of predisposed patients with no pathogenic variant identified, in search for potential 5′UTR mechanisms of gene deregulation [ 58 , 68 , 90 ]. The data generated from these studies led to the identification of some variants that demonstrated an impact on transcriptional regulation ( Table 2 ).…”
Section: Impact Of Brca1/2 Non-coding Variants mentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have screened BRCA1 and BRCA2 promoters of predisposed patients with no pathogenic variant identified, in search for potential 5′UTR mechanisms of gene deregulation [ 58 , 68 , 90 ]. The data generated from these studies led to the identification of some variants that demonstrated an impact on transcriptional regulation ( Table 2 ).…”
Section: Impact Of Brca1/2 Non-coding Variants mentioning
confidence: 99%
“…RNA sequencing revealed that the heterozygous variant that was segregated with the hypermethylated BRCA1 allele, resulting in the allelic loss of BRCA1 expression [ 83 ]. Similar to Lynch syndrome [ 90 , 91 ], this example raises the question of whether constitutional BRCA1/2 epimutations can represent an alternative mechanism for cancer predisposition. Considering that luciferase activity assay is ultimately indicative of both transcriptional and translational efficiency, it is noteworthy that, in functional studies, the reduced levels of BRCA1 protein is not always associated with reduced transcript levels [ 94 , 95 ].…”
Section: Impact Of Brca1/2 Non-coding Variants mentioning
confidence: 99%
“…Information Theory (IT) has been proven to accurately predict impact of mutations on mRNA splicing, and has been used to interpret coding and non-coding mutations that alter mRNA splicing in both common and rare diseases 3,5-15 . We have described an IT-based framework for the interpretation and prioritization of non-coding variants of uncertain significance, which has been validated in multiple studies involving novel variants in patients with history or predisposition to heritable breast and/or ovarian cancer [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Single-nucleotide DNA sequence variants within the transcriptional promoter of the BRCA1 gene (hg19; chr17:41277186–41278132 plus chr17:41276114–41276753) were analyzed for an effect on regulatory activity, using the pGL3 luciferase reporter system (Promega, WI, USA) [2]. To enable evaluation of the effect of the variants, an internal control (pGL3-promoter; Promega) was analyzed simultaneously.…”
mentioning
confidence: 99%
“…All reporter luciferase activities were normalized to Renilla activity, and subsequently to the internal control, which allowed calculation of the variance of the WT reporter. Technical replicates were averaged and treated as a single biological replicate, and statistics performed on the biological replicates [2]. …”
mentioning
confidence: 99%